Asian Qualitative Research in Tourism Ontologies, Epistemologies, Methodologies, and Methods (Perspectives on Asian Tourism,, 2018)
This book explores the ontologies, epistemologies, methodologies, and methods that inform tourism qualitative research conducted either by Asian scholars or non-Asian scholars focusing on Asia. In addition to providing a platform for researchers to publish their qualitative journeys, it aims to encourage further Asian qualitative tourism research production. The book not only includes chapters from Asian scholars but also non-Asian tourism researchers with a focus on Asia, as their chapters are crucial to represent the multiplicity of realities constituting 'Asia'. It is of interest to the whole tourism academic community as it provides novel methodological insights from a non-Western perspective, which at the moment are often silenced by dominant (Western) voices.